Woodland caribou range occupancy in northwestern Ontario: past and present - Racey, G.D.; Armstrong, T. (Rangifer, 2000)
A zone of continuous woodland caribou (Rangifer tarandus caribou) distribution is defined for northwestern Ontario. This zone establishes a benchmark for measuring the success of future management of habitat and conservation of populations. Inventory of key winter, summer and calving habitats reaffirms the concept of a dynamic mosaic of habitat tracts that supports caribou across the landscape. The historical range recession leading to this current distribution has been associated with resource development, fire and hunting activities over the past 150 years, and numerous attempts at conservation over the last 70 years. The decline was apparently phased according to several periods of development activity: i) early exploitation in the early to mid-1800s; ii) isolation and extirpation of southern populations due to rapid changes in forest use and access between 1890 and 1930; and iii) further loss of the southernmost herds due to forest harvesting of previously inaccessible areas since the 1950s. Lessons learned from history support current conservation measures to manage caribou across broad landscapes, protect southern herds, maintain caribou habitat as part of continuous range, maintain large contiguous tracts of older forest and ensure connectivity between habitat components.